Predictive Value of Early Warning Scores for Procalcitonin and CRP in Hospitalized Community-Acquired Pneumonia Patients - Pratiwi Yuliansari; Zauhani Kusnul; Agit Pratama Putra; Yuly Peristiowati (Journal Of Nursing Practice, 2025)
Background: Pneumonia is a lower respiratory tract infection that causes the most deaths worldwide. There is a lack of knowledge about the predictive value of Early Warning Score (EWS) for procalcitonin, CRP, Mortality in Community Acquired Pneumonia (CAP). Purpose: The aim of this study was to see how accurate the EWS is at predicting procalcitonin, CRP and the mortality in Community Acquired Pneumonia patients who are hospitalized. All adult patients who were hospitalized for confirmed CAP between March and June 2023 were retrospectively included. Methods: A Total of 61 confirmed CAP patients treated in Internal Medicine High Care Unit were included in the present study. Results: The results showed that EWS≥8 was equivalent to procalcitonin in the septic shock category with (OR: 4.667), while EWS≥7 was equal to high risk CRP with (OR: 5.727), and the risk of mortality (83.3%). Conclusion: Based on the data analysis test, it concluded that EWS could used as a measuring tool to predict procalcitonin and CRP values, as well as mortality risk.